Evaluation of inert gas rebreathing for determination of cardiac output: influence of age, gender and body size - Middlemiss, Jessica E.; Cocks, Alex; Paapstel, Kaido; Maki-Petaja, Kaisa M.; Sunita; Wilkinson, Ian B.; McEniery, Carmel M. (Hypertension research, 2019)
The aim of this study was to evaluate an inert gas rebreathing method (Innocor) for measurement of cardiac output and related haemodynamic variables and to provide robust normative data describing the influence of age, gender and body size on these variables. Four separate studies were conducted: measurement repeatability (study 1, n = 45); postural change (study 2, n = 40); response to submaximal cycling exercise (study 3, n = 20); and the influence of age, gender and body size (study 4, n = 1400). Repeated measurements of cardiac output, stroke volume and heart rate were similar, with low mean (±SD) differences (0.26 ± 0.53 L/min, 0 ± 11 mL and 2 ± 6beats/min, respectively). In addition, cardiac output and stroke volume both declined progressively from supine to seated and standing positions ( P < 0.001 for both) and there was a stepwise increase in both parameters moving from rest to submaximal exercise ( P < 0.001 for both). In study 4, there was a significant age-related decline in cardiac output and stroke volume in males and females, which remained significant after adjusting for body surface area (BSA, P < 0.001 for all comparisons). Both parameters were also significantly higher in those with high body mass index (BMI; P < 0.01 versus those with normal BMI for all comparisons), although indexing cardiac output and stroke volume to BSA reversed these trends. Inert gas rebreathing using the Innocor device provides repeatable measurements of cardiac output and related indices, which are sensitive to the effects of acute physiological manoeuvres. Moreover, inert gas rebreathing is a suitable technique for examining chronic influences such as age, gender and body size on key haemodynamic components of the arterial blood pressure.